Buying and Selling Online from an Islamic Legal Poin of View - S Suherlan (Apollo: Journal of Tourism and Business, 2023)
Many people, especially those who purchase and sell online, expect convenience and profit. This is because many people have discovered that buying and selling online may be just as dangerous as being subjected to scam. The goal of this research is to examine the practice of buying and selling online from the standpoint of Islamic law. This is a library research project, and the data used is secondary data from various literatures. A qualitative descriptive method is used to assess the acquired data. The findings show that Islam is a religion that helps to safeguard humanity because the norms of buying and selling are confirmed in the Al-Quran and Hadith. This is done so that humans are not enslaved by today's widespread greed and dishonesty. Online purchasing and selling transactions that follow Islamic law standards would provide progress and peace to society and the country. Buying and selling online is allowed and legitimate under Islamic law, as long as it does not include components that can harm it, such as usury, tyranny, fraud, coercion, and fraud, and satisfies the pillars and conditions of the sale and buy contract.